1966
DOI: 10.2172/4519621
|View full text |Cite
|
Sign up to set email alerts
|

Leachability of Alumina Calcine Produced in the Idaho Waste Calcining Facility

Abstract: SClENTlFlC AND TSCWNICAL INFEIRMATION. NATIONAL BUREAU OF STANDARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1969
1969
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…6 Similar levels of extraction were seen in 4 days using dilute nitric acid. She further indicated that 90% steady state leaching levels were reached in 5 and 20 days for cesium and strontium, respectively.…”
Section: Calcine Dissolution/degradation Ratementioning
confidence: 56%
“…6 Similar levels of extraction were seen in 4 days using dilute nitric acid. She further indicated that 90% steady state leaching levels were reached in 5 and 20 days for cesium and strontium, respectively.…”
Section: Calcine Dissolution/degradation Ratementioning
confidence: 56%
“…In 1966, Paige [5] performed leaching studies on aluminum calcine generated at the Waste Calcine Facility (WCF). In that work, 500 mL aliquots of 0.5 g HNO, were circulated through 20 grams of the WCF calcine at 25°C.…”
Section: Percent Dissolution Of Aluminum-type Calcinementioning
confidence: 99%
“…Three leaching curves a r e presented f o r Epon 815 and represent c a s t i n g s made from t h e products of t h r e e s e p a r a t e preparations of t h e s a l t waste from t h e standard composition s o l u t i o n described i n Table 4. The i n i t i a l leach r a t e f o r t h e s y n t h e t i c C: Na s a l t waste i t s e l f was determined t o be Q. , 19 2 cm -day Incorporation of s a l t waste i n a r e s i n matrix w i l l render t h e waste l e s s leachable f o r two reasons: (1) t h e s a l t c r y s t a l s w i l l be encapsulated i n i n s o l u b l e m a t e r i a l , and ( 2 ) t h e r e s i n -s a l t mass i s e s s e n t i a l l y impermeable t o t h e passage of water. Radioactive cesium i s r e a d i l y leached from c a l c i n e d Figure 1 4 Sodium Leach Rates of Resin-Salt-Was t e Mixtures alumina and z i r c o n i a wastes by t h e passage of water through t h e granules ( 2 9 3 ) .…”
Section: Simulated S a L T Wastementioning
confidence: 99%